Die resente geskiedenis en ontwikkeling van die Departement Godsdiens- en Sendingwetenskap (Afd A), 1979-1992 - Merwe, P. J. van der (Hervormde teologiese studies, 1992)
Recent history and the development of the Department of Science of Religion and Missiology (Sec A), 1979-1992 The ‘recent phase’ in the history of this Department started with the author’s appointment as Head in 1979. In his inaugural speech he recognised the need to restructure Science of Religion (within the Faculty of Theology) to the formal norms of theology. He visualised a theological Science of Religion which would reach its apogee in a theologia religionis and not a philosophy of religion. Recent history has seen changes in curricula to conform to Section A’s curriculum reform project (which started in the early eighties). The Department even gained a subject - Evangelistics. This article gives an overview of teaching done since 1979. Current attempts to introduce Science of Religion to the Faculty of Arts, as a non-theological subject, are outlined.